Personifikacja teorii: gry intertekstualne w „Małym światku" - Tymicka, Magdalena (Przestrzenie Teorii, 2007)
The paper tries to deal with a relationship between theory and fiction. Reading David Lodge academic novel Small World, where the conflict between structuralism and deconstruction is the plot's main theme, the author asks what happens when theory becomes a subject of a novel. Being a part of fictional discourse, turns out quite tricky for the theoretical discourse, as it could come dangerously close to irony, parody or pastishe. In-depth analysis of complicated narration levels and author's strategy in Lodge's novel is supposed to draw the reader from simple conclusions, in which literature poses an example for theory, or theory for literature. It allows to see the relation between both of these subjects as dynamic and full of contradictions, pointing at, and indicating each other's limitations.